A Byzantine Burial Cave in the vicinity of Shepherds' Field - Batz, Sh. (Liber Annuus, 2003)
Abstract A Byzantine burial cave was unearthed in the vicinity of Shepherdsʼ Field, the traditional place where angels announced the birth of Christ to the shepherds (Luke 2:8-11). The area is rich with monasteries from the Byzantine period. The present paper describes the cave and findings, and suggests that the tomb may have belonged to a monastic community.